Aportacions i referències etnopoètiques en l’obra literària de Carmelina Sánchez-Cutillas. - I. SANZ, JOAN BORJA (Scripta, 2021)
Carmelina Sánchez-Cutillas’ literary creations include abundant ethnopoetic references. These contributions are interesting not only for the study of folklore and also –and very especially– as strategic elements in the construction of discourse. The author’s memorialistic prose frequently tends to present memories wrapped in a magical mist: a kind of blurred perspective that optimizes the propensity for wonder. In this way, the reader participates in an atmosphere where it is difficult to «distinguish the real facts from the fantastic». This article studies the contributions and ethnopoetic references present in the literary texts of Carmelina Sánchez-Cutillas as an epistemiological option that is considered relevant for a better understanding of the personal, poetic and captivating game of fusions, confusions, effusions and diffusions –on the imprecise and suggestive boundaries between reality, dream, memory, imagination, history and fiction– which, in the last analysis, is the literary work of this singular author.